Legal and Ethics in Business : Navigating Key Principles and Compliance for Modern Enterprises. - Online Courses, Virversity; ProQuest (firma) (La Vergne : eBookit.com, 2025)
This book provides a comprehensive exploration of legal and ethical principles essential for modern business operations. It covers foundational topics such as contract law, business structures, employment law, intellectual property, consumer protection, and regulatory compliance. The book emphasizes the importance of ethical decision-making and risk management in maintaining corporate integrity. Designed for business professionals and students, it aims to equip readers with practical knowledge to navigate complex legal environments, resolve disputes, and ensure compliance with laws governing enterprises. The course also includes insights into international business law, environmental compliance, and effective dispute resolution strategies, offering an invaluable resource for those seeking to excel in business law and ethics.
Description based on publisher supplied metadata and other sources.
Part of the metadata in this record was created by AI, based on the text of the resource.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2026. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Business ethics; Contracts; elektronické knihy; electronic books